Satire in Indonesian political discourse on social media: A critical discourse analysis of Eko Kuntadhi's Instagram posts - Bahri, Syamsul; Dewi, Nora Ronita; Isdianto, M. Eko (Universitas Muhammadiyah Malang, 2026)
This study examines the use of satire in Eko Kuntadhi’s Instagram posts within the context of digital political discourse. While previous studies have explored satire in mass media and television, limited attention has been given to satire produced by public figures on social media platforms. This study aims to identify types of satire and analyze their communicative functions using a critical discourse approach. This research employs a qualitative method with discourse analysis. The data consist of 58 satirical statements collected through documentation techniques from Instagram posts. The analysis is based on Abrams and Harpham's classification of satire, combined with critical discourse perspectives, to examine meaning, ideology, and power relations. The findings show that Horatian satire dominates (51.7%), followed by Juvenalian (31%) and Menippean (17.2%). Horatian satire uses humor to persuade, Juvenalian satire expresses moral criticism, and Menippean satire critiques ideological patterns. The study reveals that satire operates not only as a stylistic device but also as a discursive tool that reflects ideological positioning and power relations in digital political communication. This study contributes to linguistic and discourse studies by demonstrating that satire in social media functions as a strategic mechanism for negotiating meaning, ideology, and audience engagement in digital public discourse.